Growth of Sheep of Jaisalmeri Breed under Different Systems of Grazing on Aristida - Eleusine Pasture in Arid Regions Of Rajasthan - Ahuja, L D; Prajapati, M C; Vyas, K K; Abasi, G R (Annals of Arid Zone, 2016)
As part of a project on evolving proper grazing systems for sheep OD rangelands in the arid and semi arid tracts of western Rajasthan, ramlambs of the yearlong growth rate response of the Jaisalmeri breed to four different pastoral treatments (deferred rotational, grazing) was studied on a Â·Poor’. condition rangelands, having an annual ,average rainnfall of 24].9 mm (about 70 per cent occurring during July, August and September, ]966), from July 1966 to June 1966. The.results of this study revealed that (a) different pastoral treatments did not significantly affect the growth rate of ramlambl, (b) growth on yearlong basis was 24.51 kg per (range 23.4 to 25.4 kg) animal per year, (c) seasons affected the 8rowt rate significantly, The growthÂ· rate was highest during July to October (]4.7 kg/lamb) and least during March and April.